Polyphenols from Blumea laciniata Extended the Lifespan and Enhanced Resistance to Stress in Caenorhabditis elegans via the Insulin Signaling Pathway - Tao Chen; Siyuan Luo; Xiaoju Wang; Yiling Zhou; Yali Dai; Lijun Zhou; Shiling Feng; Ming Yuan; Chunbang Ding (Antioxidants, 2021)
Blumea laciniata is widely used as a folk medicine in Asia, but relevant literature on it is rarely reported. We confirmed that polyphenol extract (containing chlorogenic acid, rutin, and luteolin-4-O-glucoside) from B. laciniata (EBL) showed strong antioxidant ability in vitro. Hence, in this work, we applied Caenorhabditis elegans to further investigate the antioxidant and anti-ageing abilities of EBL in vivo. The results showed that EBL enhanced the survival of C. elegans under thermal stress by 12.62% and sharply reduced the reactive oxygen species level as well as the content of malonaldehyde. Moreover, EBL increased the activities of antioxidant enzymes such as catalase and superoxide dismutase. Additionally, EBL promoted DAF-16, a transcription factor, into the nucleus. Besides, EBL extended the lifespan of C. elegans by 17.39%, showing an anti-ageing effect. Different mutants indicated that the insulin/IGF-1 signaling pathway participated in the antioxidant and anti-ageing effect of EBL on C. elegans.